Strategy for Implementing Religious Moderation in Islamic Education Management - Shalahuddin, M.; Arromy, Muhammad Miqdad; Mahmud, Mahmud; Erihadiana, Mohamad (CV. Tripe Konsultan, 2024)
The strategy for implementing religious moderation is the systematic steps and approaches used to integrate the values of religious moderation among today's diversity. This research aims to determine strategies for implementing religious moderation and supporting factors and inhibiting factors for its implementation in Islamic education management. This research uses qualitative method under case study. The findings of the research show that there are various programs of an Islamic Religious Education Curriculum which is full of moderation values, a program to habituate the values of moderation in daily life, a religious moderation training program for teachers, and the Strengthening Pancasila Student Profile Project activities as strategies for implementing religious moderation. Apart from that, the existence of a clear vision and mission, a strong commitment from the leadership and teaching staff, as well as active support from parents and the community are supporting factors for the implementation of religious moderation. However, limited resources and the influence of students' social environment outside of school which does not always support the values of moderation are factors inhibiting the implementation of religious moderation. In conclusion, the strategy for implementing religious moderation can be carried out with various programs and activities in intracurricular, extracurricular, co-curricular and school culture as well as optimizing supporting factors and innovating solutions to overcome factors that obstruct its implementation.